Learning Curve and Complications of Unilateral Biportal Endoscopy: Cumulative Sum and Risk-Adjusted Cumulative Sum Analysis - Xu, Jinchao; Wang, Dong; Liu, Jidan; Zhu, Chengyue; Bao, Jianhang; Gao, Wenshuo; Zhang, Wei; Pan, Hao (Neurospine, 2022)
Objective: The purpose of this study was to investigate the learning curve and complications of unilateral biportal endoscopy (UBE) in the treatment of lumbar disc herniation (LDH) and lumbar spinal stenosis (LSS).Methods: This was a retrospective cohort analysis of 197 consecutive patients who received UBE unilateral laminotomy bilateral decompression (UBE-ULBD) or lumbar discectomy (UBE-LD) surgery, including 107 males and 90 females with an average age of 64.83 ± 14.29 years. Cumulative sum (CUSUM) and risk-adjusted cumulative sum analysis (RA-CUSUM) were used to evaluate the learning curve, with the occurrence of complications defined as surgical failure, and variables of different phase of the learning curve were compared.Results: The cutoff point of learning curve of UBE surgery was 54 cases according to CUSUM analysis. The learning curve of UBE-ULBD and UBE-LD were divided into 3 phases. The first cutoff points were 31 and 12 cases, and the second cutoff point were 67 and 32 cases respectively. With the progress of the learning curve, the operation time and postoperative hospital stays decreased. The visual analogue scale and Oswestry Disability Index at the last follow-up were significantly lower than that before surgery. The incidence of surgical failure was 6.11% and began to decrease after the 89th case based on RA-CUSUM analysis. The surgical failure rate decreased from 10.11% to 2.78 after the 89th case with significant different.Conclusion: UBE surgery is effective in the treatment of LDH and LSS with low incidence of complications. But a learning curve of at least 54 cases still required for mastering UBE surgery.